"NGROWOT" TIRAKAT IN EXACT SCIENCE PERSPECTIVES, SOCIAL AND PSYCHOLOGY - Arifah, Siti Lailatul (Journal Intellectual Sufism Research (JISR), 2018)
In this modern life the tradition of ngrowot is seen by people outside the pesantren and it is probable that the santri themselves are merely rituals which are related to things that are supernatural, magical, and not scientifically explained. This study aims to find out how tirakat ngrowot when viewed from the perspective of exact science, social and psychology. In the perspective of the exact science of tirakat ngrowot can help in mastering the exact sciences, in terms of social tirakat ngrowot able to contribute to the success of food diversification programs and psychologically tirakat ngrowot able to increase emotional intelligence in a person.